MULTIMEDIA APPLICATIONS AND VIDEO MP3 player using Borland Delphi 7 - PRIATMOKO SETIAWAN; RISTYAWATI RISTYAWATI (Jurnal Sistem Informasi, 2006)
Abstract :Applications Multimedia Music And Video Player is an application that is created as a complement to one of multimedia applications among multimedia applications that have been there earlier that aims to provide an overview on how to manufacture and ease of Multimedia Applications and Video MP3 Player used as a means of learning and useful information for the general public. by presenting in the form of applications using Borland Delphi 7. Bibliography : (x + 66 + 26 Appendix)